Visibility Evaluation of Expressway–Tunnel Lighting in Consideration of Vehicle Headlights. Issue 2 (November 2015) - Hirakawa, Satoshi; Karasawa, Yoshinori; Funaki, Tsuyoshi
SUMMARY This paper quantitatively evaluates the visibility of an object on the road illuminated by vehicle headlights under tunnel lighting based on total revealing power (TRP). First, we derived the critical reflectance for drivers to detect an object on the road to calculate TRP. We then characterized the optical properties of vehicle headlights in a real tunnel and evaluated the visibility of objects illuminated by vehicle headlights and tunnel lighting. We found that the high‐beam headlights assured the visibility of reverse silhouette vision. We have shown that the visibility of the tunnel lighting mainly involves silhouette vision. It is found that the visibility of an obstacle on the road is not greatly changed depending on headlights.